The evolution of host specialisation in avian brood parasites. (15th July 2016) - Medina, Iliana; Langmore, Naomi E.
Abstract: Traditional ecological theory predicts that specialisation can promote speciation; hence, recently derived species are specialists. However, an alternative view is that new species have broad niches, which become narrower and specialised over time. Here, we test these hypotheses using avian brood parasites and three different measures of host specialisation. Brood parasites provide an ideal system in which to investigate the evolution of specialisation, because some exploit more than 40 host species and others specialise on only one. We find that young brood parasite species are smaller and specialise on a narrower range of host sizes, as expected, if specialisation is linked with the generation of new species. Moreover, we show that highly virulent parasites are more specialised, supporting findings in other host–parasite systems. Finally, we demonstrate that different measures of specialisation can lead to different conclusions, and specialisation indices should be designed taking into account the biology of each system.